MANAJEMEN KONFLIK ANTARUMAT BERAGAMA BERBASIS AL-QURAN, ETIS DAN TEKNIS - Muhammad Suaib Tahir; Abdul Jamil Wahab; Muhammad Hariyadi (LP2M Universitas PTIQ Jakarta, 2022)
This study demonstrates Quran-based Interfaith Conflict Resolution as a conflict management model that introduces and promotes the theory of nonviolence and peace-building and the principle of coexistence among religious believers. Although some verses in Quran may mention and justifies the use of limited force as in Quranic verses QS. al-Baqarah/2:190 and QS. al-Hajj/9:39, some others also present a lot of principles and the implementation of nonviolence including patience, forgiveness, tolerance, dispute prevention and management, the prohibition of seeking revenge, clarification (tabayun), dialogue, negotiation, mediation, mutual curse (mubahalah), acceptance of agreement, persuasive preaching, reconciliation, and amnesty. This study introduces the Ethical-Technical Conflict Resolution or Management model as it contains ethical and technical foundation formulas. The ethical foundation formula as the basic principles, for example, includes justice, maslahah (public interest), tolerance, and nonviolence. In the meantime, the technical foundation which is operational in nature includes dialogue, social interaction and cooperation, negotiation, mediation, peace agreement, law enforcement, reconciliation and amnesty